2018
DOI: 10.32674/jis.v8i2.138
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Identification, Acculturation, and Academic Experience Abroad: A Case of a Joint Faculty-Led Short-Term Study Abroad Program

Abstract: The number of students expanding their academic programs to include learning experiences abroad has been steadily increasing over the past two decades. This study investigates the cultural identification of short-term study abroad participants and its influence on their acculturation process. By means of a widely used acculturation scale, it was found that there were statistically significant effects of cultural experiences on cultural identification, specifically decreases in cultural identification scores. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…They found that participants' self-efficacy and cultural intelligence were higher after studying abroad than before studying abroad for monocultural individuals. As illustrated by the different results obtained by Vande Berg et al (2009) andNguyen et al (2018), if duration is a determining factor of the effectiveness of studying abroad, this topic remains controversial since some studies (e.g., Czerwionka, Artamonova, & Barnosa, 2015; Gilin & Young, 2009;Lee & Negrelli, 2018) have concluded that even short-term programs are effective while some other studies (e.g., Engle & Engle, 2004;Kehl & Morris, 2008;Medina-Lopez-Portillo, 2004) have found the opposite.…”
Section: Study Abroad Programs and Intercultural Competencementioning
confidence: 99%
See 1 more Smart Citation
“…They found that participants' self-efficacy and cultural intelligence were higher after studying abroad than before studying abroad for monocultural individuals. As illustrated by the different results obtained by Vande Berg et al (2009) andNguyen et al (2018), if duration is a determining factor of the effectiveness of studying abroad, this topic remains controversial since some studies (e.g., Czerwionka, Artamonova, & Barnosa, 2015; Gilin & Young, 2009;Lee & Negrelli, 2018) have concluded that even short-term programs are effective while some other studies (e.g., Engle & Engle, 2004;Kehl & Morris, 2008;Medina-Lopez-Portillo, 2004) have found the opposite.…”
Section: Study Abroad Programs and Intercultural Competencementioning
confidence: 99%
“…study abroad programs have on students. These components are exemplified by interculturality (Jackson, 2018), cultural resistance (Lemmons, 2015), independence and self-confidence (Walsh & Walsh, 2018), cultural competency (Hermond, Vairezm, & Tanner, 2018), awareness of cultural diversity (Wooldridge, Peet, & Meyer, 2018), intercultural competence (Deardorff, 2009;Yarosha, Lukic, & Santibáñez-Gruber, 2018), self-efficacy and cultural intelligence (Nguyen, Jefferies, & Rojas, 2018), contact with host-society (Matera, Imai, & Pinzic, 2018;Rodriguez & Chornet-Roses, 2014), cultural adjustment (Basow & Gaugler, 2017) and acculturation process (Lee & Negrelli, 2018). This study differs from these existing studies by using a different perspective to focus on the impact of study abroad programs on developing one's intercultural competence.…”
mentioning
confidence: 99%
“…Students from different identity groups have different experiences abroad; realization of minority status can heighten awareness of students' identity within the group and can cause further stress (Savicki & Cooley, 2011). The destination of Vietnam, a developing country vastly different from the United States, provides a contrasting perspective, which enables increased cognitive dissonance resulting in the current data (Lee & Negrelli, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Different researchers see different components of intercultural competence developed through study abroad programs. Such components identified in recent works include a sense of self (Harper, 2018), cultural resistance (Lemmons, 2015), independence and self-confidence (Walsh and Walsh, 2018), awareness of cultural diversity (Wooldridge et al, 2018), intercultural competence (Deardorff, 2015a; Hanada, 2019), self-efficacy and cultural intelligence (Nguyen et al, 2018), contact with the host society (Matera et al, 2018), and the acculturation process (Lee and Negrelli, 2018). Although there is no authoritative academic definition of the competence for mutual understanding universally accepted in the relevant literature, it can be understood that it includes at least three essential elements: cognitive, affective, and behavioral (Bennett, 2011: 3).…”
Section: Methodsmentioning
confidence: 99%